Transforming Reflective Learning in Teacher Education: The Role of Metacognitive Dynamics in Adaptive Gamified Systems - Surata, I Ketut; Widiatsih, Asri; Mahmud, Nurhamsa; Suardi, Suardi; Irawan, I Putu Redy (Asian Journal of Applied Education (AJAE), 2025)
Developing reflective competence in pre-service teachers is essential for fostering critical and adaptive thinking, yet conventional methods often fall short in promoting deep metacognitive awareness. This quantitative study employed a quasi-experimental design involving 120 education students from two Indonesian universities, divided into experimental and control groups. Data were gathered through pre- and post-tests, observations, and perception questionnaires, and analyzed using ANCOVA. Findings revealed that integrating metacognitive elements into adaptive gamification significantly enhanced students' reflective competence compared to traditional methods.The results suggest that gamification tailored to metacognitive levels can effectively stimulate meaningful reflection. This study contributes to the theory of adaptive, technology-based learning models and offers practical insights for improving reflection-focused teacher education curricula.